Brazil: ten years of refugee protection - Maria Beatriz Nogueira; Carla Cristina Marques (Forced Migration Review, 2008)
The international solidarity and responsibility sharing evidentin refugee protection in Brazil contrast sharply with therestrictive trends seen in many other countries.